A novel null mutation in the pyruvate dehydrogenase phosphatase catalytic subunit gene (PDP1) causing pyruvate dehydrogenase complex deficiency. Issue 1 (17th June 2019) - Bedoyan, Jirair K.; Hecht, Leah; Zhang, Shulin; Tarrant, Stacey; Bergin, Ann; Demirbas, Didem; Yang, Edward; Shin, Ha Kyung; Grahame, George J.; DeBrosse, Suzanne D.; Hoppel, Charles L.; Kerr, Douglas S.; et al.
Abstract: Congenital lactic acidosis due to pyruvate dehydrogenase phosphatase (PDP) deficiency is very rare. PDP regulates pyruvate dehydrogenase complex (PDC) and defective PDP leads to PDC deficiency. We report a case with functional PDC deficiency with low activated (+dichloroacetate) and inactivated (+fluoride) PDC activities in lymphocytes and fibroblasts, normal activity of other mitochondrial enzymes in fibroblasts, and novel biallelic frameshift mutation in the PDP1 gene, c.575dupT (p.L192FfsX5), with absent PDP1 product in fibroblasts. Unexpectedly, the patient also had low branched‐chain 2‐ketoacid dehydrogenase (BCKDH) activity in fibroblasts with slight elevation of branched‐chain amino acids in plasma and ketoacids in urine but with no pathogenic mutations in the enzymes of BCKDH, which could suggest shared regulatory function of PDC and BCKDH in fibroblasts, potentially in other tissues or cell types as well, but this remains to be determined. The clinical presentation of this patient overlaps that of other patients with primary‐specific PDC deficiency, with neonatal/infantile and childhood lactic acidosis, normal lactate to pyruvate ratio, elevated plasma alanine, delayed psychomotor development, epileptic encephalopathy, feeding difficulties, and hypotonia. This patient exhibited marked improvement of overall development following initiation of ketogenic diet at 31 months of age. To the best of our knowledge, this is the fourth case of functional PDC deficiency with a defined mutation in PDP1 . Synopsis: Pyruvate dehydrogenase phosphatase (PDP) regulates pyruvate dehydrogenase complex (PDC) and defective PDP due to PDP1 mutations leads to PDC deficiency and congenital lactic acidosis.